2002
DOI: 10.1021/je010299g
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Data for the Exchange of Cu2+, Cd2+, and Zn2+ Ions for H+ on the Cationic Exchanger Amberlite IR-120

Abstract: Equilibrium ion-exchange isotherms of H + /Cu 2+ , H + /Cd 2+ , and H + /Zn 2+ on a strong acid resin, Amberlite IR-120, in an aqueous medium at (283 and 303) K have been determined in order to assess the possibility of using ion exchange to eliminate heavy-metal ions from industrial aqueous liquid streams. The experimental equilibrium data have been satisfactorily correlated using the homogeneous mass action law model (LAM). This model assumes nonideal behavior for both the solution and solid phases. Wilson a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 9 publications
(16 reference statements)
1
29
1
Order By: Relevance
“…This behaviour agrees with that shown in Part I of this paper by the strongly acidic cationexchanger Amberlite 252. 29 The fitting process gave the same maximum ion-exchange capacity, q 0 = 5.0 mmol protons g −1 dry resin, found by Valverde et al 30 for the ions Cu 2+ , Cd 2+ and Zn 2+ but a little lower than the values reported by Carmona et al 31 for removal of the ions Pb 2+ , Ni 2+ and Cr 3+ using this resin in aqueous media. As in Part I, 29 it is important to point out that this result agrees with previous work indicating that the presence of water at any concentration in a mixture with an organic solvent favours salt ionization and furthers the accessibility of the counter ions to the resin active sites and thus, the capacity of the resin known to be fully accessible in pure organic solvents is completely available in glycerol-water mixtures.…”
Section: Resultssupporting
confidence: 76%
“…This behaviour agrees with that shown in Part I of this paper by the strongly acidic cationexchanger Amberlite 252. 29 The fitting process gave the same maximum ion-exchange capacity, q 0 = 5.0 mmol protons g −1 dry resin, found by Valverde et al 30 for the ions Cu 2+ , Cd 2+ and Zn 2+ but a little lower than the values reported by Carmona et al 31 for removal of the ions Pb 2+ , Ni 2+ and Cr 3+ using this resin in aqueous media. As in Part I, 29 it is important to point out that this result agrees with previous work indicating that the presence of water at any concentration in a mixture with an organic solvent favours salt ionization and furthers the accessibility of the counter ions to the resin active sites and thus, the capacity of the resin known to be fully accessible in pure organic solvents is completely available in glycerol-water mixtures.…”
Section: Resultssupporting
confidence: 76%
“…The same heavy metal/hydrogen ion exchange systems using IR-120 at different temperatures were also studied by Valverde et al (2002). Unlike this study, Valverde et al used the Wilson and Pitzer equations to calculate the activity coefficients in the resin and liquid phases, respectively.…”
Section: Ion-exchange Equilibriamentioning
confidence: 99%
“…(1) Computational and experimental adsorption data shows that the dry resin's adsorption capacity for Pb 2+ and Ni 2+ ions is 5.56 meq/g (Carmona et al 2008), while for Cu 2+ and Cd 2+ ions it is 5.0 meq/g (Valverde et al 2002). Thus, by adding magnetite to the system, the adsorption capacity of the resin slightly reduced in case of Cu 2+ , Ni 2+ , and Cd 2+ ions, but improved for Pb 2+ .…”
Section: Adsorption Tests Of the Synthesized Magnetic Polymer Beadsmentioning
confidence: 99%